Perceptions and reported use of extended reality technology in Royal College-Accredited Canadian Simulation Centres: a national survey of simulation centre directors - Tokuno, Junko; Bilgic, Elif; Gorgy, Andrew; Harley, Jason M (Canadian Medical Education Journal, 2024)
Background: Extended reality technology (XR) in simulation-based medical education is becoming more prevalent. This study examined Canadian simulation centre directors’ perceptions toward XR and their self-reported adoption of XR within their centres. Methods: We conducted a national, cross-sectional survey study to examine five kinds of XR: Immersive Virtual Environments, Screen-based Virtual Worlds, Virtual Simulators, Immersive Augmented Reality, and Non-immersive Augmented Reality. An electronic survey with multiple-choice, Likert scales, and open-ended questions were developed to identify the current use, degree of satisfaction, and experienced and foreseen challenges with each XR technology. We used the Checklist for Reporting Results of Internet E-Surveys checklist to describe and justify our survey development. All twenty-three Royal College-accredited Canadian simulation centres were invited based on their Royal College membership to complete the survey. Directors and representatives of seventeen (74%) centres participated. Results: Each XR has been used for research or simulation education by about half of the simulation centres, at minimum. The degree of satisfaction among directors with XR ranged from 30% to 45%. Directors frequently cited logistical and fidelity challenges, along with concerns over maintenance. Cost and lack of evidence, and unclear needs were cited as foreseen challenges with the future implementation of XRs. Conclusions: This survey summarizes the status of XR in Canadian simulation centres. The pattern of use, satisfaction levels, and challenges reported by simulation centre directors varied depending on the types of XR.